Clinical Impact of RANK Signalling in Ovarian Cancer - Verena Wieser (Cancers, 2019)
Ovarian cancer (OC) is a gynaecological malignancy with poor clinical outcome and limited treatment options. The receptor activator of nuclear factor-κB (RANK) pathway, activated by RANK ligand (RANKL), critically controls bone metabolism, tumourigenesis and tumour immune responses. Denosumab, a monocloncal RANKL antibody, exerts tumour-suppressive effects in mice and humans. Here, we investigated the relevance of RANK signalling in OC. RANK, RANKL and OPG expression in 192 epithelial OC tissues was compared to expression in 35 non-malignant control tissues and related to clinico-pathological characteristics. Findings were validated in a cohort of 563 OC patients from The Cancer Genome Atlas (TCGA). The expression of RANK, RANKL and OPG was studied in four OC cell lines and the impact of RANK ligation or blockade on OC cell proliferation was determined. RANK, RANKL and OPG were expressed in epithelial and stromal cells in OC. RANKL expression was elevated in OC tissue, particularly in BRCA1/2 mutated tumours. High RANKL expression independently predicted reduced progression-free (PFS, p = 0.017) and overall survival (OS, p = 0.007), which could be validated in the TCGA cohort (PFS, p = 0.022; OS, p = 0.046, respectively). Expression of RANK and OPG in OC cells was induced by inflammatory cytokines IL-1β and TNFα. Neither recombinant RANK ligation nor denosumab treatment affected OC cell proliferation. Our study independently links RANKL expression with poor clinical outcome in two unrelated OC cohorts. These findings implicate RANK signalling in the immunopathogenesis of OC and warrant clinical trials with denosumab in OC.